Congenital vitiligo: A case observed in the cohort of HIV-exposed infants in Bobo-Dioulasso, Burkina Faso - Makoura Barro; Jean W. Diallo; Ad Bafa Ibrahim Ouattara; Boubacar Nacro (MDPI AG, 2017)
Vitiligo is a dermatological disease; its exact prevalence is unknown among the paediatric population. We are reporting a case of vitiligo at birth for the first time in Burkina Faso, in the Teaching Hospital Souro Sanou of Bobo-Dioulasso, Paediatric Department. He is a male child, born from HIV-1 positive parents; we received him when he was 2 months to be followed in connection with the prevention of motherto- child transmission. He showed achromic lesions on the skin and on skin appendages at birth. In addition to congenital vitiligo we mentioned, several diagnostic hypotheses were discussed. No treatment was decided to face these skin lesions given the very young age of the patient. Psychological support is planned in the long run.